The synthesis of 3,5-disubstituted indolizidines - Cheesman, Penelope, Sue (My University, 1996)
Aspects of the literature of the ant venom alkaloid monomorine I and its stereoisomers were reviewed. Racemic 5-butyl-2-pyrrolidinone was synthesised in two steps from methyl acrylate and 1-nitropentane, A thionation step yielded 5-butylpyrrolidine-2-thione. The Michael addition reaction between 5-butylpyrrolidine-2-thione and ethyl crotonate proceeded with difficulty to form a separable mixture of diastereomers of 5-butyl-l-(2-ethoxycarbonyl-l-methylethyl) pyrrolidine-2-thione. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. January 1996.
Keywords: Indole alkaloids--Synthesis; Organic compounds--Synthesis